KALANG DI DALAM PRASASTI-PRASASTI MATARAM KUNA, ABAD VIII-X M : IDENTIFIKASI NILAI BUDAYA MASYARAKAT JAWA - Richadiana Kartakusuma (Berkala Arkeologi, 2000)
In line with the pace of modernization and development in all fields, there has been tremendous growth in various sectors of life. The situation resulted in the emergence of transformation and shift in socio-cultural, economic and political values. It seems that Kalang and his wisdom actually survive with his traditional values that used to be the knots of strength that sent these people from time to time. These people are flexible to accompany the changes of the times without having to lose its personality in the midst of the environment affected by the modernization era.